The Role of Emotional Intelligence in Time Management Among Managers of Sports Institutions in Iraq - Hussein, Mustafa Hameed (Indonesian Journal of Sport, Health and Physical Education Science, 2025)
Background of Study: This study investigates the relationship between emotional intelligence and time management among managers of sports institutions in Iraq. Emotional intelligence is considered a critical factor in enhancing managerial performance and optimizing organizational efficiency, while time management is a key competency in achieving administrative effectiveness. Methods: The study applied a descriptive survey method with a sample of 125 managers from the Iraqi Ministry of Youth and Sports. Two scales were developed—emotional intelligence (20 items) and time management (20 items)—which were validated through expert judgment, discriminant analysis, internal consistency, and Cronbach’s alpha reliability tests. Data were analyzed using t-tests, Pearson correlation, and simple regression. Result: Findings revealed that both emotional intelligence and time management scores were significantly higher than the theoretical mean (p < 0.001). A strong positive correlation (r = 0.980, p < 0.001) was found between emotional intelligence and time management. Regression analysis indicated that emotional intelligence significantly predicted time management effectiveness, explaining 95.9% of its variance. Conclusion: Emotional intelligence plays a pivotal role in enhancing time management among sports managers. The study recommends integrating emotional intelligence development into organizational culture and training programs to improve time utilization, administrative efficiency, and overall performance in sports institutions.